MAKNA SIMBOL PANCA JIWA (Analisis Semiotika Roland Barthes) - Nujhan, M. Rifai (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
Many meanings are contained in one word that is spoken or written so that it is not interpreted. The research raises the meaning of the Five Souls of Modern Darussalam Gontor Cottage (PMDG) as the object of research. Because the five souls of the media have messages, language, and meanings related to the signs in the life of the students of each sign have relations, so that it produces meaning that depends on the perspective of the text reader, this study aims to find the meaning of the five souls of PMDG. This study used a literature study. The study of signs or semiotics, researchers used Roland Barthes’s semiotic analysis of signified, signifier, denotative, connotative and also myths. This study found meaning as follows: soul sincerity means sincere lill, simplicity does not mean destitute, selfsufficient able to work alone, Ukhuwwah Islam a way of socializing and freedom as an act of values that includes all the arrangements that animate the cottage so as not to get out of bounds. This research is expected to be able to help improve students’ understanding of the five PMDG souls, so that at least become a developer for the progress of Pondok.